Analysis of Students’ Mathematical Reasoning Abilities in Solving Linear Equation in Two Variables on Android Game Called Ganjaran - Muhammad Arif Purnomo; Ahmad Lubab; Agus Prasetyo Kurniawan (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2022)
Game Penjelajah Ruang (The Space Exploration Game, Ganjaran) is a learning media in the form of an Android-based educational game to practice the mathematical reasoning skills of class VIII students on SPLDV questions. The purpose of this study was to describe students' mathematical reasoning abilities in solving SPLDV questions on Android-based of Ganjaran. The students' mathematical reasoning ability can be seen from the results of working on the SPLDV questions by students which are made based on mathematical reasoning indicators. The type of research used is descriptive qualitative research. The subjects of this study were students of class VIII SMP Negeri 2 Krian as many as 4 students who had played the Ganjaran. The test instrument used in this study was a 5-point SPLDV reasoning question with short answers. From the results of the study, the average value of students' mathematical reasoning abilities was 56.25 which was quite sufficient. Overall, the indicator of mathematical reasoning ability that is mostly mastered by students is indicator c (drawing conclusions, compiling evidence, providing reasons or evidence for the correctness of the solution), while the indicator of student mathematical reasoning that is less mastered by students is indicator a (proposing conjectures).